DivIVA Interacts with the Cell Wall Hydrolase MltG To Regulate Peptidoglycan Synthesis in Streptococcus suis - Jiang, Qinggen; Li, Boxi; Zhang, Liangsheng; Li, Tingting; Hu, Qiao; Li, Haotian; Zou, Wenjin; Hu, Zhe; Huang, Qi; Zhou, Rui (Microbiology spectrum, 2023)
The peptidoglycan (PG) biosynthesis pathway provides a rich source of novel antimicrobial drug targets. However, bacterial PG synthesis and its regulation is a very complex process involving dozens of proteins. Bacterial morphology is largely determined by the spatial and temporal regulation of peptidoglycan (PG) biosynthesis. Ovococci possess a unique pattern of PG synthesis different from the well studied Bacillus , and the mechanism of the coordination of PG synthesis remains poorly understood. Several regulatory proteins have been identified to be involved in the regulation of ovococcal morphogenesis, among which DivIVA is an important one to regulate PG synthesis in streptococci, while its mechanism is largely unknown. Here, the zoonotic pathogen Streptococcus suis was used to investigate the regulation of DivIVA on PG synthesis. Fluorescent d -amino acid probing and 3D-structured illumination microscopy found that DivIVA deletion caused abortive peripheral PG synthesis, resulting in a decreased aspect ratio. The phosphorylation-depleted mutant (DivIVA 3A ) cells displayed a longer nascent PG and became longer, whereas the phosphorylation-mimicking mutant (DivIVA 3E ) cells showed a shorter nascent PG and became shorter, suggesting that DivIVA phosphorylation is involved in regulating peripheral PG synthesis. Several DivIVA-interacting proteins were identified, and the interaction was confirmed between DivIVA and MltG, a cell wall hydrolase essential for cell elongation. DivIVA did not affect the PG hydrolysis activity of MltG, while the phosphorylation state of DivIVA affected its interaction with MltG. MltG was mislocalized in the Δ divIVA and DivIVA 3E cells, and both Δ mltG and DivIVA 3E cells formed significantly rounder cells, indicating an important role of DivIVA phosphorylation in regulating PG synthesis through MltG. These findings highlight the regulatory mechanism of PG synthesis and morphogenesis of ovococci. IMPORTANCE The peptidoglycan (PG) biosynthesis pathway provides a rich source of novel antimicrobial drug targets. However, bacterial PG synthesis and its regulation is a very complex process involving dozens of proteins. Moreover, unlike the well studied Bacillus , ovococci undergo unusual PG synthesis with unique mechanisms of coordination. DivIVA is an important regulator of PG synthesis in ovococci, while its exact role in regulating PG synthesis remains poorly understood. In this study, we determined the role of DivIVA in regulating lateral PG synthesis of Streptococcus suis and identified a critical interacting partner, MltG, in which DivIVA influenced the subcellular localizations of MltG through its phosphorylation. Our study characterizes the detailed role of DivIVA in regulating bacterial PG synthesis, which is very helpful for understanding the process of PG synthesis in streptococci.